Colon capsule endoscopy in colorectal cancer screening: Interim analyses of randomized controlled trial CareForColon2015 - Ulrik Deding; Thomas Bjørsum-Meyer; Lasse Kaalby; Morten Kobaek-Larsen; Marianne Kirstine Thygesen; Jeppe Buur Madsen; Rasmus Kroijer; Gunnar Baatrup (Endoscopy International Open, 2021)
Background and study aims The Danish CareForColon2015 trial, launched in 2020 as part of the Danish Colorectal Cancer Screening program, is the largest randomized controlled trial to date on colon capsule endoscopy (CCE). This paper presents the interim analysis with the objective of ensuring the safety of patients in the intervention group and evaluating the clinical performance of the trial’s predefined clinical parameters. Patients and methods We evaluated the initial 234 CCEs according to quality, safety, and completion. The participation rates and preference distribution of all individuals invited were analyzed and sample size calculations were adjusted. Results Fecal immunochemical test and diagnostic participation rates were 62.1 % and 91.1 %, respectively. The completion rate for CCEs was 67.9 % and the rate of conclusive investigations was 80.3 %. The polyp detection rate (PDR) was high (73.5 %), only two (0.85 %) technical failures in 234 videos were observed, and six suspected cancers were identified (2.6 %). No major adverse events were recorded. The required number of invitations had been underestimated due to inaccurate assumptions in sample size calculations. Conclusions The trial was efficient and safe in terms of CCE quality and time to diagnostic investigation. Participation rates and PDRs were high. The proportion of suspected cancers was lower than expected and will be followed. The completion rate for CCEs was acceptable but lower than expected and the CCE procedure was reviewed for potential improvements and Resolor was added to the regime. The number of invitations for the intervention group of the trial has been adjusted from 62,107 to 185,153.